2016
DOI: 10.1038/srep26857
|View full text |Cite
|
Sign up to set email alerts
|

An RNA-aptamer-based two-color CRISPR labeling system

Abstract: The spatial organization and dynamics of chromatin play important roles in essential biological functions. However, direct visualization of endogenous genomic loci in living cells has proven to be laborious until the recent development of CRISPR-Cas9-based chromatin labeling methods. These methods rely on the recognition of specific DNA sequences by CRISPR single-guide RNAs (sgRNAs) and fluorescent–protein-fused catalytically inactive Cas9 to label specific chromatin loci in cells. Previously, multicolor chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 24 publications
3
79
0
4
Order By: Relevance
“…Shorter and simpler guide-RNA 9 for Cpf1 could potentially be deleterious for its engineering or extension, as is done for Cas9's guide-RNA 39 . For e.g., an extra 5' guanine in the guide-RNA was extremely deleterious for LbCpf1 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Shorter and simpler guide-RNA 9 for Cpf1 could potentially be deleterious for its engineering or extension, as is done for Cas9's guide-RNA 39 . For e.g., an extra 5' guanine in the guide-RNA was extremely deleterious for LbCpf1 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction as a biological tool, the CRISPR/Cas9 system has been harnessed to create model organism genetic knockouts (KO), label chromatin, and even modulate gene activity (Dahlman et al, 2015; Konermann et al, 2015; Platt et al, 2014; Sung et al, 2014; Wang et al, 2016). Advantages of the CRISPR/Cas9 system include its ease of use and versatility, making it the tool of choice for genetic manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the RNA‐binding viral proteins MCP and PCP can be labelled with different colours via fluorescent proteins so that two distinct targets can be visualized simultaneously. As in Yi Fu's study, Siyuan Wang conducted analogous research and found that extending the tetraloop and stem loop 2 of the sgRNA with MS2 or PP7 aptamers can increase the signal‐to‐background ratio of chromatin imaging. In the meantime, Hanhui Ma et al proposed an approach similar to but more advanced than the above method.…”
Section: Applications To Detecting Specific Sequences Of Dna or Rnamentioning
confidence: 82%